Etika Profesi Guru Pendidikan Agama Islam Sebagai Sistem Kontrol di Era 5.0 - Junaidin Junaidin (eL-HIKMAH: Jurnal Kajian dan Penelitian Pendidikan Islam, 2023)
Teacher ethics are essential to ensure the efficient and effective operation of education. Educators play a crucial role in fostering the growth and development of students' potential. This article aims to explore the significance of ethics as both a value and a control system for professionals in the field of Islamic religious education during the 5.0 era. The research method employs a qualitative approach by conducting a literature review. Scientific references, including books, journals, and encyclopedias, as well as the Law on Teachers and Lecturers, are used to emphasize the importance of ethics for Islamic religious educators. The importance of ethical conduct for Islamic religious education teachers within the teaching profession is encompassed by five standards of ethical behavior. These standards include: (1) ethics toward oneself, where teachers must exhibit patience, dedication, and seek support from family; (2) ethics toward students, as teachers are role models and represent the future of education, and must possess refined personal competencies fortified by ethical standards; (3) ethics toward student guardians; (4) ethics toward colleagues; (5) ethics toward society; and (6) ethics toward religion. This aspect requires teachers to demonstrate politeness, authority, activeness, and proficiency in collaborating with colleagues, superiors, parents, and the community, in order to efficiently perform the profession of Islamic education. Abstrak: Etika guru adalah fondasi penting untuk memastikan berjalannya pendidikan dengan lancar dan efektif. Guru memiliki peran kunci dalam mendorong pertumbuhan dan perkembangan potensi peserta didik. Artikel ini bertujuan untuk membahas urgensi etika sebagai sebuah nilai dan system kontrol profesi guru pendidikan agama Islam era 5.0. Metode penelitian menggunakan studi pustaka dengan pendekatan kualitatif. Referensi-referensi ilmiah berupa buku, jurnal, ensiklopedia dan Undang-undang Guru dan Dosen digunakan untuk menyederhanakan urgensi etika bagi seorang pendidik agama Islam. Urgensi etika guru pendidikan agama Islam terkait profesi keguruan, ada lima yang menjadi ruang lingkup etika keguruan, yakni; (1) etika terhadap diri sendiri, di mana guru harus bersikap sabar, sepenuh hati dalam tugasnya, dan mendapatkan dukungan dari keluarga; (2) etika terhadap peserta didik, guru harus menjadi teladan dan cerminan pendidikan masa depan, dengan kompetensi kepribadian yang baik yang diperkuat oleh etika; (3) etika terhadap wali murid; (4) etika terhadap rekan sejawat; (5) etika terhadap masyarakat; (6) etika terhadap agama. Aspek terakhir ini menuntut guru memiliki sikap yang sopan, berwibawa, aktif, dan kemampuan kerja sama yang baik, baik dengan rekan sekerja, atasan, orang tua, maupun masyarakat, demi menjalankan profesi pendidikan Islam dengan efektif.